An Implementation of Automated Excel-Based Accounting Applications at BUM Desa - Iskandar; Kodirin; Siswanto (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to teach basic accounting skills and introduce simple, automated Excel-based applications for preparing financial reports of village-owned businesses. The community service method is implemented in several stages with a combination of online and offline activities. Training and mentoring will be conducted online and offline and attended by directors and treasurers of all BUM Desa in East Belitung. Support is provided at BUM Desa sites and delivered to BUM Desa selected by the Office of Social Affairs, Community Empowerment, and the villages of East Belitung District. Community service achievements include improving basic accounting skills, implementing an automated Excel-based accounting application, and producing BUM Desa financial reports that meet standards.